(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study aims to describe the form and meaning of uslub nahyi in Surah Al-Baqarah by using the method of documentation and recording. This method is done by reviewing a number of documents and literature related to the research. The documents analyzed can be in the form of literature sources such as books, journals and articles related to the problem to be studied. Based on the documents that have been processed, 37 words are obtained which are scattered in 28 verses in the form of fi’il mudhari which is preceded by La Nahiyah/Lam Nahi. The meaning of uslub nahyi in Surah Al-baqarah is: the meaning of tahdid (threatening) totaling 9 words, the meaning of irsyad (guidance or guidance) totaling 18, and the meaning of Do’a (request) totaling 1 word.